Cerebral venous thrombosis following an immunoglobulin-E mediated anaphylactic reaction - Dias da Costa, Mariana; Nascimento Alves, Pedro; Aguiar de Sousa, Diana; Canhão, Patrícia (Journal of stroke and cerebrovascular diseases, 2023)
Prothrombotic and pro-inflammatory states are known cerebral venous thrombosis risk factors. To date, two cases of venous thrombotic events after immunoglobulin-E mediated anaphylaxis have been reported. Herein, we describe the first case of cerebral venous thrombosis in close temporal relation with an immunoglobulin-E mediated anaphylactic event. A 51-year-old female presented with headache, language, and mental disturbance lasting for two days. Two days before the onset, she had undergone a provocative test with deflazacort to study an allergy history; after the test she developed a severe anaphylactic reaction. There were no other comorbidities, and in addition to contraceptive pill, she did not take other medications. On admission the patient was drowsy, with anomic aphasia, inattention and memory impairment. Magnetic Resonance Imaging depicted a left caudate and lenticulo-capsulo-thalamic venous infarct and thrombosis in the deep venous system. The patient was treated with anticoagulation and showed progressive improvement. Neoplastic and pro-thrombotic diseases were excluded. The close temporal association between the anaphylactic reaction and cerebral venous thrombosis suggests that anaphylactic reaction could have been a cerebral venous thrombosis precipitating factor. Immunoglobulin-E have been suggested to have prothrombotic activity by stimulating the release of platelet activation factor, thromboxane A2 and serotonin. This case adds on to the available information on possible cerebral venous thrombosis associated conditions.